Impact of gradient zero-valent iron pollution from steel works on soil microaggregate geochemical processes and dissipative structures - Li, Chunjie; Xu, Wenbo; Guo, Shili; Shang, Songhao; Li, B. Larry (Frontiers in Environmental Science, 2024)
Abstract: Zero-valent iron (ZVI) contamination from steel works poses significant threats to soil quality and ecosystem health, particularly affecting soil microaggregates, which are fundamental to soil structure and function. In this study, we systematically investigated the impact of gradient ZVI pollution on the organic geochemical environment of soil microaggregates around steel works located in the core water source area of the Middle Route of the South-to-North Water Diversion Project in China. Advanced analytical techniques, including X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), X-ray fluorescence spectroscopy (XRF), inductively coupled plasma optical emission spectroscopy (ICP-OES), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR), were employed to comprehensively characterize the geochemical processes, mineralogy, and organic matter environment of soil microaggregates. The findings revealed that soils near the steel works were acidified and strongly oxidized, with heavy metal contents, particularly Fe, significantly decreasing with increasing distance from the steel works (Fe content decreased from 27,516.2 mg/kg to 23,492.6 mg/kg). The pH of soils near the steel works was lower, while oxidation-reduction potential (ORP) and electrical conductivity were higher. XPS analysis indicated a higher content of reactive oxygen species (ROS) near the steel works and significantly lower soil organic matter content. The iron valence distribution showed spatial differences, with higher Fe2⁺ content on the surface of soil microaggregates near the steel works and Fe³⁺ dominating in areas farther away. These results suggest an evolutionary sequence of ZVI from Fe (0) oxidation to Fe(II) and then to Fe(III). The formation of dissipative structures in soil microaggregates due to ZVI contamination significantly affects soil physicochemical properties and the organic environment. This study provides valuable insights into the multifaceted impacts of industrial activities on soil ecosystems and offers a scientific basis for soil conservation and remediation strategies.